PENERAPAN PENDEKATAN PEMBELAJARAN RECIPROCAL TEACHING PADA MATERI OPERASI HITUNG PECAHAN DI KELAS VII SMP SWASTA LKIA PONTIANAK - Sofia, Tika Sayyidah; R, Zubaidah; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aims to know and describe the teacher?s class management, student?s learning activities, student?s respond and student?s outcomes in the implementation of reciprocal teaching approach in the operation of fraction topic at class VII SMPS LKIA Pontianak. The research method is descriptive method. The form of research is preexperiment with One Shot Case Study design.The research subjects are 15 students. Based on data analysis that review four aspects, the results are : (1) the teacher?s class management categorized very good with an average score 3,94; (2) student?s learning activities categorized active withan average percentage score 83%; (3) student?s respond categorize positive with percentage score 81%; and (4) student?s outcome is not reached classical completeness with only 67% of student can achieve the criteria of minimum completeness. Because only three out of four aspects that achieved, the conclusion of this research is the implementation of reciprocal teaching approach is not effective to apply in the operation of fraction topic at class VII SMPS LKIA Pontianak. Keywords : Reciprocal Teaching, Effectiveness, Operation Of Fraction